Differences in risk factors for children with special health care needs (CSHCN) receiving needed specialty care by socioeconomic status - Bae Sejong; Fulda Kimberly G; Lykens Kristine A; Singh Karan P (BMC, 2009)
Abstract Background The purpose of this study is to identify factors affecting CSHCN's receiving needed specialty care among different socioeconomic levels. Previous literature has shown that Socioeconomic Status (SES) is a significant factor in CHSHCN receiving access to healthcare. Other literature has shown that factors of insurance, family size, race/ethnicity and sex also have effects on these children's receipt of care. However, this literature does not address whether other factors such as maternal education, geographic location, age, insurance type, severity of condition, or race/ethnicity have different effects on receiving needed specialty care for children in each SES level. Methods Data were obtained from the National Survey of Children with Special Health Care Needs, 2000-2002. The study analyzed the survey which studies whether CHSCN who needed specialty care received it. The analysis included demographic characteristics, geographical location of household, severity of condition, and social factors. Multiple logistic regression models were constructed for SES levels defined by federal poverty level: < 199%; 200-299%; ≥ 300%. Results For the poorest children (,199% FPL) being uninsured had a strong negative effect on receiving all needed specialty care. Being Hispanic was a protective factor. Having more than one adult in the household had a positive impact on receipt of needed specialty care but a larger number of children in the family had a negative impact. For the middle income group of children (200-299% of FPL severity of condition had a strong negative association with receipt of needed specialty care. Children in highest income group (> 300% FPL) were positively impacted by living in the Midwest and were negatively impacted by the mother having only some college compared to a four-year degree. Conclusion Factors affecting CSHCN receiving all needed specialty care differed among socioeconomic groups. These differences should be addressed in policy and practice. Future research should explore the CSHCN population by income groups to better serve this population